2014
DOI: 10.2106/jbjs.j.00947
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Eversion During Total Knee Replacement

Abstract: The results of this trial showed that retracting rather than everting the patella during total knee arthroplasty resulted in no significant clinical benefit in the early to medium term. We observed no increase in patellar tendon shortening as a result of eversion rather than subluxation. Our findings did suggest that, with subluxation, there may be an increased risk of damage to the patellar tendon and reduced visualization of the lateral compartment, leading to an increase in implant malpositioning with later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 30 publications
3
64
0
Order By: Relevance
“…Umrani et al [52] in 2013, found that patellar eversion did not significantly affect quadriceps recovery after TKA up to 1 year after surgery. In the most recent study, Reid et al [53] in 2014 found that patients who underwent TKR with patella eversion had similar clinical outcome 3 mo and 1 year postoperatively with patients who had TKR with patellar subluxation. They also noted that patellar subluxation may lead to an increased risk of damage to the patella tendon and increase in tibial component malpositioning.…”
Section: Patellar Eversion or Not?mentioning
confidence: 99%
See 1 more Smart Citation
“…Umrani et al [52] in 2013, found that patellar eversion did not significantly affect quadriceps recovery after TKA up to 1 year after surgery. In the most recent study, Reid et al [53] in 2014 found that patients who underwent TKR with patella eversion had similar clinical outcome 3 mo and 1 year postoperatively with patients who had TKR with patellar subluxation. They also noted that patellar subluxation may lead to an increased risk of damage to the patella tendon and increase in tibial component malpositioning.…”
Section: Patellar Eversion or Not?mentioning
confidence: 99%
“…Reid et al [53] Prospective randomized double-blinded study. Patients undergoing TKA through a standard medial parapatellar approach assigned to either retraction or eversion of the patella groups…”
Section: Ref Type Of Study Outcomementioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have been conducted with the aim of comparing the relative effect of patellar eversion with patellar noneversion during TKA, and the results have been included in numerous meta-analyses with the aim of summarizing the outcomes of this approach and delineating the clear guidelines based on the available evidences. [7][8][9][10][11][12][13][14][15] However, a 2016 review by Jia et al concluded that "patellar eversion and patellar non-eversion could achieve similar results," 9 whereas Yang et al analyzed the same RCTs concluded that "patellar non-eversion offers a shorter hospital stay and a lower incidence of postoperative complications." 8 Despite this scenario could appear paradoxical, it could represent an important source of confusion when clinicians aim to implement evidence-based approach in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…This checklist was produced with surgical interventions, among others, in mind, and raises the issues of surgeons' relevant experience in procedures, as well as differences between procedures in terms of their difficulty. Consequently, it recommends reporting, “Details of how the interventions were standardized.” None of the trials included in this sample actually reference this statement (only eight of the 44 papers published in 2009 or later make any reference to CONSORT at all), and then just in relation to the provision of a flowchart of participants, but there might be a general, tacit influence of improved reporting standards at play. Finally, there are significant associations between good or poor reporting of the surgeon's experience domain and good or poor reporting of allocation concealment and attrition within this set of RCTs, but there are no other significant associations between the surgeon domain and others.…”
Section: Discussionmentioning
confidence: 99%